O6.4VX-970, selective inhibitor of ataxia telangiectasia and Rad3-related (ATR) protein. (17th March 2015) - Asmal, M.; Dean, E.; Evans, J.; Middleton, M.; Plummer, R.
Abstract : Background : ATR is a critical regulator of the homologous recombination DNA repair pathway and the cellular response to replication stress. Inhibition of ATR is predicted to selectively enhance the sensitivity of tumor cells, in which DNA repair is often compromised, to standard of care DNA damaging agents, while relatively sparing non-tumor cells which have DNA repair mechanisms to compensate for the loss of ATR. VX-970 is a potent and selective inhibitor of ATR with a Ki < 0.2 nM and intracellular IC50 of 19 nM. Results : VX-970 substantially increases the cytotoxic activity of multiple DNA damaging agents in a broad panel of tumor cell lines, with minimal increase in non-tumor cell cytotoxicity. VX-970 markedly synergizes with cytotoxic agents in mouse xenograft models of several tumor types. At concentrations of VX-970 which inhibit tumor growth, phosphorylation of the downstream biomarker, Chk1, is observed, as is up-modulation of markers of unrepaired double strand DNA breaks, including gamma-H2AX. VX-970 is currently in two phase 1 clinical trials which employ standard 3 + 3 dose escalations in subjects with advanced solid tumors to determine the tolerability of escalating doses of VX-970, administered intravenously, in combination with gemcitabine, cisplatin or carboplatin. Conclusions : VX-970 is an inhibitor of ATR that enhances the activity of DNA damaging agents in pre-clinical models, and is in phase 1 clinical development.